An overview on the development of conventional and alternative extractive methods for the purification of agarose from seaweed. Issue 3 (11th February 2018) - Chew, Kit Wayne; Juan, Joon Ching; Phang, Siew Moi; Ling, Tau Chuan; Show, Pau Loke
ABSTRACT: This overview describes the development of the classical and alternative methodologies used for the extraction of agarose from seaweed. The first mentioned methods for agarose extraction, including acetylation of agar, methylation and extraction using polyether compounds, do not show high yield or good quality of agarose extract-product. Besides that, they ceased to be eco-friendly. The low level of their environmental sustainability has led to the development of alternative technologies to produce agarose in a more purified, ecological and cost-effective manner. Examples of these methods include mainly ionic liquid (IL)-based or bio-IL-based extraction. This review is aimed at providing a survey on agarose extraction techniques and methods related to biomolecules separation.